2000
DOI: 10.1007/s004640000248
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic antireflux surgery: comparative study of Nissen, Nissen-Rossetti, and Toupet fundoplication

Abstract: The results of this study do not differ significantly from the data reported in the literature, suggesting such surgical techniques are effective and well tolerated, and that both can be properly used in the treatment of GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 16 publications
2
39
1
3
Order By: Relevance
“…Patti [43] analysed the long-term results of patients treated with partial versus total antireflux procedures: efficacy was higher for total fundoplication (recurrence of reflux in 4% of patients with total fundoplication versus 19% in patients with partial fundoplication), while the incidence of postoperative dysphagia was similar in both groups, even in patients with impaired esophageal peristalsis (8% Toupet versus 9% Nissen). Pessaux [44] , at a three-month follow-up, noted a dysphagia rate of 4.2% in patients treated with Nissen fundoplication versus 5.9% with Nissen-Rossetti wrap and 6.9% in those treated with Toupet. In a prospective randomized trial, Bessell [45] concluded that calibrating the antireflux wrap according to esophageal motility was not necessary, because the postoperative persistent dysphagia rate was similar between patients with total or partial wrap.…”
Section: Discussionmentioning
confidence: 99%
“…Patti [43] analysed the long-term results of patients treated with partial versus total antireflux procedures: efficacy was higher for total fundoplication (recurrence of reflux in 4% of patients with total fundoplication versus 19% in patients with partial fundoplication), while the incidence of postoperative dysphagia was similar in both groups, even in patients with impaired esophageal peristalsis (8% Toupet versus 9% Nissen). Pessaux [44] , at a three-month follow-up, noted a dysphagia rate of 4.2% in patients treated with Nissen fundoplication versus 5.9% with Nissen-Rossetti wrap and 6.9% in those treated with Toupet. In a prospective randomized trial, Bessell [45] concluded that calibrating the antireflux wrap according to esophageal motility was not necessary, because the postoperative persistent dysphagia rate was similar between patients with total or partial wrap.…”
Section: Discussionmentioning
confidence: 99%
“…8,89,90 Surgeons began to perform partial fundoplications more frequently, 11,91 and the results of several nonrandomized trials did not confirm this hypothesis. [92][93][94] On the other hand, some authors still cast serious doubts regarding the effectiveness of partial fundoplication on the control of reflux, 93,[95][96][97] and others suggest that a floppy Nissen can be effective even in patients with defective esophageal peristalsis. 98,99 In this analysis (Table 6), partial fundoplication appeared to be a better procedure than total fundoplication, showing similar operative time, morbidity and recurrence rates, but a significantly reduced rate of reoperations for failure (1.6% versus 9.6%), mainly due to postoperative dysphagia (10.1% versus 16.8%).…”
Section: Annals Of Surgery • Volume 239 Number 3 March 2004mentioning
confidence: 99%
“…After the development of laparoscopic access described by Geagea 7 and Dallemagne et al 8 , the fi rst reports suggested the routine SGV division to reduce postoperative dysphagia 9,10,11 . However, other researches did not had the same results 12,13,14,15 . The randomized clinical trials (RCT) during laparoscopic era present now different standards of technique: the mobilization extension, number of divided vessels and the technique to make those divisions.…”
Section: Introductionmentioning
confidence: 84%